(untitled) (Chemical Engineering Research Bulletin, 2008)
This work is concerned with the combustion phenomena of high ash content and swamp-type peat-char particles obtained from Kola-Mouza in Bangladesh. The influence of reaction temperature (450- 700Â°C), particle size (0.7-6. 7mm) and air flow rate (50-150 1/h) on the rate of peatchar-02 reaction was studied in a laboratory scale reactor. The burning rate of the peat-char particles was found to be directly proportional to temperature and air flow rate and inversely proportional to particle diameter. This study has revealed that the peatcher-O2 reaction proceeds uniformly throughout the interior surfaces of the particle and that ash layer resistance starts influencing the reaction rate when peat-char bed inlet temperature exceeds 500Â°C. Chemical Engineering Research Bulletin 11 (2007) 1-18